Evidence Based Nutrition: knowledge and use among dietitians of Pakistan - Saeed, Ayesha (Progress in Nutrition, 2017)
Background: Evidence Based Practice, a relatively new term in Pakistan; is pivotal to achieve optimum patient care and satisfaction. Most of the healthcare providers, including dietitians are unaware of its importance. The objective of the study was to identify knowledge and use of Evidence Based Nutrition (EBN) among dietitians of Pakistan. Methods/subjects: A cross sectional survey was carried out and structured, pretested questionnaires were e-mailed to the dietitians working in Pakistan. The response rate was 45% (23/51). Mean age of the respondents was 29.134 years and mean years of practice were 4.347. 87% (n=20) were females and 52.2% (n=12) had 16 years of education.34.8% (n=8) were registered dietitians and 47.8% (n=11) were employed full time as dietitians across Pakistan. Results: 82.6% (n=19) reported to engage in research activities and 60.9% (n=14) stated to use EBN in their practice. 52.2% (n=12) sometimes encountered knowledge gaps; for 60.9% (n=14) these were related to MNT and 78.2% (n=18) performed their own literature search on internet. Almost half (48%) had access to evidence based libraries and 52.2% (n=12) reported to use them. Reported barriers to implement EBN were lack of skills for critical appraisal of articles (39.1%, n=9); lack of knowledge of EBN (43.5%, n=10); and lack of time (8.7%, n=2). Main source of information was internet 65.2% (n=15). All of them were of the view that EBN should be used in routine clinical practice. Conclusion: It can be concluded that there is a lack of knowledge and use of EBN among dietitians in Pakistan. Providing adequate on-job training to current dietitians and incorporating EBN in nutrition and dietetics curriculum will enable future practitioners to implement EBN.